The benefit of GLP-1RA in different age groups in the cardiovascular outcome trials. (July 2021) - Younes, Ahmed M.; Mishriky, Basem M.; Powell, James R; Cummings, Doyle M
Highlights: There may be hesitancy in prescribing GLP-1RA in older adults. GLP-1RAs were associated with lower incidence of MACE regardless of baseline age. GLP-1RAs should be considered in appropriately selected older adults. Abstract: There may be hesitancy in prescribing GLP-1RA in older adults. On pooling results from the CVOTs comparing GLP-1RA to placebo, there was a significantly lower incidence of MACE favoring GLP-1RA in both younger and older adults. GLP-1RA should be considered in high risk patients regardless of age.